2010
DOI: 10.1136/bcr.08.2010.3284
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal fistula associated with bevacizumab 20 months after mediastinal radiation

Abstract: Correspondence to Hideto Yamada, otedih@belle.shiga-med.ac.jp DESCRIPTIONWe report a case of a 60-year-old woman who developed a tracheal fistula 20 months after mediastinal radiation while being treated with bevacizumab. She presented with a large right-sided mediastinal mass given a diagnosis of stage IIIB adenocarcinoma. She was treated with definitive thoracic radiation (figure 1) and a concurrent chemotherapy, including both cisplatin and docetaxel. Eleven months after chemoradiotherapy she developed prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It has been documented before that bevacizumab, a commonly used antiangiogenic agent, given together with dose-intensive radiotherapy carries a risk of severe and unusual toxicity once irradiating the mucosal organs such as bronchi, intestines, and urethra [38][39][40][41] . The detrimental effect on the mucosa, mostly with hypofractionated high dose regimens, seemed to be true notwithstanding the order and time between the radiotherapy and bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented before that bevacizumab, a commonly used antiangiogenic agent, given together with dose-intensive radiotherapy carries a risk of severe and unusual toxicity once irradiating the mucosal organs such as bronchi, intestines, and urethra [38][39][40][41] . The detrimental effect on the mucosa, mostly with hypofractionated high dose regimens, seemed to be true notwithstanding the order and time between the radiotherapy and bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from these studies indicate that the addition of an antiangiogenic agent to the chemoradiotherapy regimen may cause more adverse effects compared with that caused by chemoradiotherapy alone. Adverse events induced by bevacizumab, such as tracheoesophageal fistulae, were even reported 20‐21 months after chemoradiotherapy in patients with lung cancer, making long‐term follow‐up periods in these patients necessary . The authors indicated that even a history of mediastinal RT using high‐dose radiation may be a risk factor for the development of life‐threatening fistulae upon receiving bevacizumab.…”
Section: Discussionmentioning
confidence: 99%